Lignin Quantification of Papyri by TGA—Not a Good Idea - Florian Bausch; Dickson D. Owusu; Paul Jusner; Mario J. Rosado; Jorge Rencoret; Sabine Rosner; José C. del Río; Thomas Rosenau; Antje Potthast (Molecules, 2021)
Papyri belong to the oldest writing grounds in history. Their conservation is of the highest importance in preserving our cultural heritage, which is best achieved based on an extensive knowledge of the materials’ constituents to choose a tailored conservation approach. Thermogravimetric Analysis (TGA) has been widely employed to quantify cellulose and lignin in papyrus sheets, yielding reported lignin contents of 25% to 40%. In this work, the TGA method conventionally used for papyrus samples was repeated and compared to other lignin determination approaches (Klason-lignin and acetyl bromide-soluble lignin). TGA can lead to a large overestimation of the lignin content of commercial papyrus sheets (~27%) compared to the other methods (~5%). A similar overestimation of the lignin content was found for the pith and rind of the native papyrus plant. We concluded that the TGA method should, therefore, not be used for lignin quantification.